2012
DOI: 10.7314/apjcp.2012.13.5.2399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Tumor Associated Material (TAM) with Conventional Biomarkers in Cancer Patients

Abstract: Objective: To compare expression level of serum tumor associated materials (TAM) with several conventional serum tumor biomarkers, eg., carcinoembryonic antigen (CEA), carbohydrate antigen19-9 (CA19-9), carbohydrate antigen 15-3 (CA15-3), alpha-fetoprotein(AFP), in selected solid tumors. Methods: Patients diagnosed histologically or cytologically with liver, breast, esophageal, gastric, colorectal or pancreatic cancers were enrolled into this study. After diagnosis, the level of TAM was determined by chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The above hypothesis test was a two-sided test; P<0.05 was considered as statistically significant. We have enough experience in conducting medical researches, and have published some results elsewhere Yan et al, 2011;Zhang et al, 2011;Gong et al, 2012;Liu et al, 2012;Gu et al, 2013;Shu et al, 2012;Xu et al, 2012;Xu et al, 2012;Yu et al, 2012;Zhang et al, 2012;Chen et al, 2013;Dai et al, 2013;Deng et al, 2013;Huang et al, 2013;Lu et al, 2013;Sun et al, 2013;Wei et al, 2013;Wu et al, 2013;Yang et al, 2013;.…”
Section: Statistical Methods and Research Experiencementioning
confidence: 99%
“…The above hypothesis test was a two-sided test; P<0.05 was considered as statistically significant. We have enough experience in conducting medical researches, and have published some results elsewhere Yan et al, 2011;Zhang et al, 2011;Gong et al, 2012;Liu et al, 2012;Gu et al, 2013;Shu et al, 2012;Xu et al, 2012;Xu et al, 2012;Yu et al, 2012;Zhang et al, 2012;Chen et al, 2013;Dai et al, 2013;Deng et al, 2013;Huang et al, 2013;Lu et al, 2013;Sun et al, 2013;Wei et al, 2013;Wu et al, 2013;Yang et al, 2013;.…”
Section: Statistical Methods and Research Experiencementioning
confidence: 99%
“…Each point on the ROC curve represents a determined threshold. Statistical analyses were performed using IBM SPSS statistics 19.0 for Windows (SPSS Inc; IBM, Chicago, IL).We have published medical researches that were conducted in Jiangsu Cancer Center elsewhere Yan et al., 2011; Zhang et al, 2011; Gong et al, 2012;Liu et al, 2012; Gu et al, 2013;Li et al, 2012;Shu et al, 2012; Zhan et al, 2012; Zhan et al, 2012;Xu et al, 2012;Xu et al, 2012;Yu et al, 2012; Zhang, et al, 2012; Zhang et al, 2012; Chen et al, 2013; Dai et al, 2013; Deng et al., 2013; Liu et al, 2013; Liu et al, 2013; Liu et al, 2013; Lu et al, 2013;Sun et al, 2013;Wei et al, 2013;Wu et al, 2013;Yang et al, 2013; …”
mentioning
confidence: 99%
“…These results suggested that macrophage-like THP-1 cells facilitate angiogenesis in tumors to provide rapidly proliferating transformed-cells much more oxygen and nutrients. The proangiogenic role of TAMs has been characterized by previous studies that showed the correlation between TAMs infiltration and high number of vascular in many tumors, such as squamous cell carcinoma of the esophagus, prostate cancer and ameloblastoma (Koide et al, 2004;Halin et al, 2009;Guzman-Medrano et al, 2012), the main reason for this may be that TAMs produce many cytokines for angiogenesis: vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), TNF-α, transforming growth factor-β (TGF-β) (Bingle et al, 2006;Araujo et al, 2010;Shu et al, 2012), and several angiogenesis-modulating enzymes, such as matrix metalloproteinases (MMP) (Pollard, 2004;Kale et al, 2014). The fact that the specific proangiogenic program in tumor turns on indicated that tumor is in a condition of hypoxic, rendering tumor cells to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%